1997
DOI: 10.1093/jn/127.7.1349
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Amylose Cornstarch Is More Digestible than Soluble Amylopectin Potato Starch in Rats ,

Abstract: In liquid enteral formulations, high molecular weight soluble starches may be able to replace glucose and low molecular weight glucose polymers that have high glycemic indices. Male rats were fed either commercial cornstarch, dextrose, modified soluble potato (70-75% amylopectin) starch, or modified soluble amylomaize-7 (70% amylose) starch for 4 wk. Body weights did not differ among the groups. Food consumption was significantly higher in the two modified starch-fed groups than in the two control groups. Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…As for liver weight of the animals, no differences were observed in the organ's weight in response to diets with different digestibilities (KABIR et al, 1998;KIM et al, 2003), while others (ZHOU & KAPLAN, 1997) observed that liver weight was significantly lower in the low digestibility diets, thought no effect of the amylose:amylopectin ratio was observed. In the present study, liver weight also did not correlate with the amylose:amylopectin ratio in rice grains, since the treatments with low (MOCHI) and high (IRGA 417) amylose content presented higher organ's weights.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…As for liver weight of the animals, no differences were observed in the organ's weight in response to diets with different digestibilities (KABIR et al, 1998;KIM et al, 2003), while others (ZHOU & KAPLAN, 1997) observed that liver weight was significantly lower in the low digestibility diets, thought no effect of the amylose:amylopectin ratio was observed. In the present study, liver weight also did not correlate with the amylose:amylopectin ratio in rice grains, since the treatments with low (MOCHI) and high (IRGA 417) amylose content presented higher organ's weights.…”
Section: Resultsmentioning
confidence: 82%
“…However, ZHOU & KAPLAN (1997), evaluating the digestibility of two starch sources, potato with 70-75% amylopectin and maize with 70% amylose, in an experiment with rats during four weeks, also observed significantly greater feed intake with the high amylopectin diet, although no effect was seen on body weight gain. Usually rice grains with low amylose content are more palatable (RAMIREZ, 1991), which can explain the higher feed intake that, associated with the higher digestibility of amylopectin, influenced the body weight gain of the animals.…”
Section: Resultsmentioning
confidence: 94%
“…The digestion of starch depends on its amylose-amylopectin ratio and their molecular weight (Granfeldt et al, 1994; Englyst and Hudson, 1996). Amylose has more hydrogen bonds and undergoes more rapid retrogradation than does amylopectin (Zhou and Kaplan, 1997), while the amylopectin, having a branched chain, allows a greater access to digestive enzymes. For this reason, amylose is more resistant to hydrolytic enzymes compared with amylopectin (Kabir et al, 1998; Weurding et al, 2001), which may be partly attributed to the presence or development of resistance starch (Behall and Hallfrisch, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects on growth in response to dietary amylose were observed in pigs (Cohen and Tanksley, 1973), poultry (Pirgozliev at al., 2000; Gutierrez Del Alamo et al, 2009) and goats (Kyuma and Ishida, 1989), but the negative effects were observed in rats (Aziz et al, 2009; Denardin et al, 2012), pigs (Perez and Aumaitre, 1979; Camp et al, 2003), and poultry (Ertl and Dale, 1997; Bergh et al, 1999; Pirgozliev et al, 2002; Collins et al, 2003; Pirgozliev at al., 2010). No effect of starch type on growth was also observed in rats (Mongeau et al, 1995; Zhou and Kaplan, 1997; Kabir et al, 1998) and pigs (Shelton et al, 2004). In fish, Rawles and Lochmann (2003) first investigated the starch utilization related to starch type and observed an enhanced growth of sunshine bass ( Morone chrysops ♀ × M. saxatilis ♂ ) when fed with a diet at the higher ratio of amylose-amylopectin starch.…”
Section: Introductionmentioning
confidence: 91%
“…Segundo Rooney & Pflugfelder (1986) e Kabir et al (1998), a digestibilidade do amido é, em geral, inversamente proporcional ao seu conteúdo de amilose, mas, Zhou & Kaplan (1997) observaram em ratos que o amido de batata (70-75% de amilopectina) teve digestibilidade inferior ao amido do milho (70% de amilose).…”
Section: Introductionunclassified